MARPLE: software for multiphysics modelling in continuous media - Gasilov, Vladimir A.; Boldarev, Alexey S.; Olkhovskaya, Olga G.; Boykov, Dmitriy S.; Sharova, Yulia S.; Savenko, Nikita O.; Kotelnikov, Alexey M. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2023)
The research code MARPLE was originally created to model high-speed dynamic processes caused by the action of high-intensity energy fluxes on matter. At present, it is a universal tool able to solve various continuum mechanics problems. The implemented physical models are the following: single-fluid two-temperature MHD model of plasma dynamics, including electron-ion energy exchange and generalized Ohm’s law; model of electrical and thermal conductivity taking into account the anisotropy in the magnetic field; radiative heat transfer: models pertinent to optically thin as well as optically thick media: techniques for taking into account radiative cooling losses, spectral multigroup diffusion transfer, laser radiation propagation etc.; model of multicomponent flow. The MARPLE code utilises modern computational technologies based on block structured and unstructured meshes. MARPLE works as MPI application for modern HPC systems. The paper presents examples of problems in plasma dynamics, magnetohydrodynamics, astrophysics, and solid thermomechanics solved by means of the MARPLE code.